2022
DOI: 10.3390/mi13020149
|View full text |Cite
|
Sign up to set email alerts
|

High Cycle Stability of Hybridized Co(OH)2 Nanomaterial Structures Synthesized by the Water Bath Method as Anodes for Lithium-Ion Batteries

Abstract: Cobalt oxides have been intensely explored as anodes of lithium-ion batteries to resolve the intrinsic disadvantages of low electrical conductivity and volume change. However, as a precursor of preparing cobalt oxides, Co(OH)2 has rarely been investigated as the anode material of lithium-ion batteries, perhaps because of the complexity of hydroxides. Hybridized Co(OH)2 nanomaterial structures were synthesized by the water bath method and exhibited high electrochemical performance. The initial discharge and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…After fitted, the strong Co 2p peaks were observed at 781.5 eV and 797.5 eV with a spin‐orbit splitting of 16.0 eV, which was in good agreement with the Co 2p signal of CoO [39–40] . The “Sat.” peaks were situated ~6.0 eV higher relative to the main peaks of Co 2p [41] . The satellite structure at this value was characteristic of the Co 2+ in CoO, which was well discussed in the previous literature [42–44] .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…After fitted, the strong Co 2p peaks were observed at 781.5 eV and 797.5 eV with a spin‐orbit splitting of 16.0 eV, which was in good agreement with the Co 2p signal of CoO [39–40] . The “Sat.” peaks were situated ~6.0 eV higher relative to the main peaks of Co 2p [41] . The satellite structure at this value was characteristic of the Co 2+ in CoO, which was well discussed in the previous literature [42–44] .…”
Section: Resultssupporting
confidence: 84%
“…peaks were situated ~6.0 eV higher relative to the main peaks of Co 2p. [41] The satellite structure at this value was characteristic of the Co 2 + in CoO, which was well discussed in the previous literature. [42][43][44] No Co 0 and Co 3 + valence state was observed in CF@CoO composite.…”
Section: Resultssupporting
confidence: 76%
“…The binding energies of Co@MXene C 1s (Figure h) are located at 286.30, 283.51, and 282.34 eV, corresponding to three bonding states C–O, C–C, and C–Ti–T x , respectively. To further understand the Co@MXene after alkali treatment, the high-resolution spectra of O 1s (Figure i) are analyzed and there are two fitted peaks located at 529.35 and 530.71 eV, which are compatible with the presence of −OH bonds and the combination of Co 2+ with −OH. , It is presumed that some of the −F end groups in the composites are substituted by −OH. This result further revealed that the alkali treatment could change the surface morphology of the composites and facilitate the formation of hydrogen bonds between MXene and Co 2+ , thereby improving the stability of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, nanosheets and nanoparticles are electrostatically self-assembled to construct Co@MXene composites with porous structures, and the reversible capacity after 120 cycles is 1283.2 mA h g –1 at a current density of 0.1 A g –1 , which is much higher than the theoretical specific capacities of Ti 2 C 3 T x MXene (320 mA h g –1 ) and Co(OH) 2 (576 mA h g –1 ) capacity. , This is attributed to the fact that, first, the transverse grain size of MXene is reduced by alkali treatment, which can dramatically promote the penetration of the electrolyte and greatly shorten the ion and electron transport paths. Second, the folded laminar structure of MXene with a 2D laminar structure can utilize more active centers for adsorbing and desorbing lithium ions, thus having a higher pseudo-capacitance contribution.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing demand for electric energy, electric energy storage has attracted increasing attention from researchers [ 1 , 2 , 3 ]. There are several electric energy storage sources, including aqueous Zn–ion batteries [ 4 , 5 ], lithium–selenium batteries [ 6 ], Li–ion batteries [ 7 , 8 ], Zn–air batteries [ 9 ], ammonium-ion batteries [ 10 ], and supercapacitors (SCs) [ 11 , 12 , 13 ]. Among them, SCs possess useful characteristics such as ultrahigh power density, long lifetime, and environmental sustainability, and thus, they have become promising electrical energy storage materials for portable electronics and other electric devices [ 14 ].…”
Section: Introductionmentioning
confidence: 99%